2014
DOI: 10.1111/1365-2745.12324
|View full text |Cite
|
Sign up to set email alerts
|

Tropical rabbitfish and the deforestation of a warming temperate sea

Abstract: Summary 1.A striking example of climate-mediated range shifts in marine systems is the intrusion of tropical species into temperate areas world-wide, but we know very little about the ecological consequences of these range expansions. 2. In the Mediterranean Sea, the range expansion of tropical rabbitfishes that first entered the basin via the Suez Canal provides a good example of how tropical herbivorous fish can impact the structure of rocky bottoms in temperate seas. Two species of rabbitfishes have now bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
168
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 57 publications
(105 reference statements)
5
168
1
Order By: Relevance
“…We propose that a reduction in resilience, combined with increased consumption rates of adult kelp and growing populations of grazers targeting lower abundances of kelp recruits, led to the observed phase shift in benthic community structure. Although such synergistic effects of warming remain to be confirmed, these findings are consistent with a growing body of literature that shows how the full suppression of large seaweeds on reefs is mediated by increases in herbivore functional diversity and feeding complementarity among herbivores (18,21,27).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We propose that a reduction in resilience, combined with increased consumption rates of adult kelp and growing populations of grazers targeting lower abundances of kelp recruits, led to the observed phase shift in benthic community structure. Although such synergistic effects of warming remain to be confirmed, these findings are consistent with a growing body of literature that shows how the full suppression of large seaweeds on reefs is mediated by increases in herbivore functional diversity and feeding complementarity among herbivores (18,21,27).…”
Section: Discussionsupporting
confidence: 86%
“…A recent review identified 80 species of tropical and subtropical herbivorous fishes expanding their ranges into temperate reefs in association with polewardflowing boundary currents around the globe (16). The impacts of these warmwater herbivores can be much greater than those of native species, as documented in the eastern Mediterranean (17,18).…”
mentioning
confidence: 99%
“…Given, however, the strong alterations in ecosystem structure, the establishment of the MPA will have to be accompanied by early restoration actions targeting the decrease (and if possible removal) of invasive species. Therefore, priority should be given to management measures for the regulation of the two herbivore fishes that have led to severe deforestation of the infralittoral rocky shores of Santorini Island, as well as other locations in the southern Aegean Sea (Bianchi et al, 2014;Vergés et al, 2014;authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, if canopy-forming macroalgae are replaced by corals, then biodiversity may be retained or increase [76]. In the eastern Mediterranean, a shift away from macroalgae has led to a loss of over 60% of benthic biomass and species richness [43]. The ecosystem services provided by a new suite of species will change, and management practices will need to adapt to shifts in resource use by humans [77].…”
Section: (C) Macroalgal Disease and Microbesmentioning
confidence: 99%